SYNTHESIS OF HIGH-QUALITY AROMATIC COMPOUNDS THROUGH COAL TAR PROCESSING (Eureka Journal of Education & Learning Technologies, 2026)
Coal tar is an important by-product of the coal carbonization process and serves as a valuable raw material for the production of aromatic compounds. These compounds play a significant role in the chemical, pharmaceutical, dye, and polymer industries. The present study aims to analyze the technological approaches used for the synthesis of high-quality aromatic compounds through coal tar processing. The research focuses on the composition of coal tar, processing methods, and the efficiency of obtained aromatic fractions. The results demonstrate that optimized distillation and purification techniques significantly improve the yield and quality of aromatic compounds. The findings highlight the industrial relevance of coal tar processing as a sustainable source of valuable chemical products.
Keywords: Coal tar, aromatic compounds, synthesis, distillation, chemical processing